Alternative promoter usage at the Notch1 locus supports ligand-independent signaling in T cell development and leukemogenesis - Gómez-del Arco, Pablo (2010)
Loss of Ikaros has been correlated with Notch activation in T cell acute lymphoblastic leukemia (T-ALL), however, the mechanism remains unknown. We identified promoters in Notch1 that drive expression of Notch1 proteins active in the absence of ligand. Ikaros bound to both canonical and alternative Notch1 promoters and its loss increased permissive chromatin, facilitating recruitment of transcription regulators. At early stages of leukemogenesis, increased basal expression from the canonical and 5’-alternative promoters initiated a feed-back loop, progressively augmenting Notch1 signaling. Ikaros also repressed intragenic promoters that are cryptic in wild-type, poised in pre-leukemic, and active in leukemic cells and which also produced ligand-independent Notch1 proteins. Only ligand-independent Notch1 isoforms were required for Ikaros-mediated leukemogenesis. Notch1 alternative-promoter usage was observed at stages of T cell development dependent on Notch signaling and during T-ALL progression. These studies identify a network of epigenetic and transcriptional regulators that control conventional and unconventional Notch signaling during normal development and leukemogenesis.